Comparative Response of Hay versus Green Fodder and Loose Versus Barn House on Feed, Nutrient and Water Intake in Murrah Buffalo Heifers - A.K. Saini (Indian Journal of Animal Nutrition, 2024)
The present study was undertaken to investigate the effect of hay versus green fodder and loose versus barn house on nutrient intake in buffalo heifers. Twenty heifers based on equal body weight and age were divided into four treatment groups; T1- conventional barn housing +hay and concentrate mixture (CM); T2- conventional barn housing + seasonal green fodder and CM; T3- loose housing +seasonal green fodder and CM; and T4 - loose housing +hay and CM during February 1st, 2004 to May 31st, 2004. The interactive relationship between two housing and feeding systems was also studied. No significant difference in daily dry matter intake (DMI), DMI per 100 kg body weight and DMI/kg W0.75 in various treatments was reported and the interactive effect of two feeding and housing systems was also non-significant. The daily crude protein intake (CPI); CPI per 100 kg B. wt. and CPI/kg W0.75 remained statistically similar among various treatments. The effect of interactions due to both housing and feeding systems was also non-significant. Similar trend was also observed with regard to daily TDN intake, TDN intake per 100 kg body weight and TDN intake per/kg W0.75. Loose housing along with hay and concentrate feeding (T4) resulted in higher (P<0.05) daily voluntary water intake (VWI), VWI/kg DM consumed and VWI/kg W0.75. Housing systems had no significant effect on daily (VWI), VWI/kg DM consumed and VWI/kg W0.75. However, feeding systems had significant effect on daily VWI,VWI / kg DM consumed and VWI / kg W0.75. Daily TWI, TWI per kg DM consumed and TWI/kg W0.75 was higher (P<0.05) due to green fodder feeding as compared to that of hay feeding system which was due to the higher moisture content in green fodder compared to that of hay. It was concluded that DM, CP and TDN intakes remained uninfluenced due to various treatments; and two feeding and housing systems. Voluntary water intake was significantly (P<0.05) higher in hay feeding than green fodder feeding; and total water intake was significantly (P<0.05) higher in green fodder feeding than hay feeding system and remained uninfluenced due to housing systems.